I'm going on a dragon hunt - Jones, Maurice (London : Puffin, 1987)
A child's wonderings take him through tall grass, across a wide ravine, over a mud field, and eventually to a cave where it seems a dragon duvells.
Keywords: Dragons -- Fiction